Understanding Tourist-Resident Contact and the Role of Contact Theory in Tourism Research - Younis Mohammad Malik (Journal of Social Responsibility, Tourism and Hospitality, 2023)
Contact between tourists and locals is an important part of exchanging knowledge and travel experiences at a destination. Nonetheless, the status of contacts in tourism development and how it may affect the tourist-resident relationship remain unknown. Tourist-resident contact is not given enough attention in tourism despite its significant effects on tourists’ travel attitudes, behaviours, and long-term perspectives. This research study focuses on the concept of tourist-resident contact at a tourism destination and provides an overview of recent advances in tourist-resident contact research. This study adds to the theoretical understanding of contact theory by expanding on the concept of tourist-resident contact in terms of contact backgrounds, contact types, and contact impacts affecting touristresident relationships at a tourist destination.